New user? Sign up

Existing user? Sign in

please can anyone solve this problem FIND - x

-2abx = a^2(b+x) + b^2(a+x) + x^2(a+b)

Note by Palash Som 2 years, 10 months ago

Sort by:

Answer is given below { a }^{ 2 }b+{ a }^{ 2 }x+{ b }^{ 2 }a+{ b }^{ 2 }x+{ x }^{ 2 }a+{ x }^{ 2 }b+2abx=0 { x }^{ 2 }(a+b)+ab(a+b)+x({ a }^{ 2 }+{ b }^{ 2 }+2ab)=0 (a+b)(x+a)(x+b)=0 x=-a or -b

Log in to reply

Hint:- Rearrange as \( a^2x + b^2x + 2abx + a^2b + b^2a + x^2(a+b) = 0 \).

help!!

Problem Loading...

Note Loading...

Set Loading...

## Comments

Sort by:

TopNewestAnswer is given below { a }^{ 2 }b+{ a }^{ 2 }x+{ b }^{ 2 }a+{ b }^{ 2 }x+{ x }^{ 2 }a+{ x }^{ 2 }b+2abx=0 { x }^{ 2 }(a+b)+ab(a+b)+x({ a }^{ 2 }+{ b }^{ 2 }+2ab)=0 (a+b)(x+a)(x+b)=0 x=-a or -b

Log in to reply

Hint:- Rearrange as \( a^2x + b^2x + 2abx + a^2b + b^2a + x^2(a+b) = 0 \).

Log in to reply

help!!

Log in to reply